2023
DOI: 10.3390/jcm12052007
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis in Adolescents with Obstructive Anomalies of the Reproductive Tract

Abstract: Background: This study aimed to assess the prevalence and course of endometriosis in adolescents with obstructive Müllerian anomalies. Methods: The study group involved 50 adolescents undergoing surgeries (median age 13.5 (range 11.1–18.5)) for rare obstructive malformations of the genital tract: 15 girls had anomalies associated with cryptomenorrhea and 35 were menstruating. The median follow-up period was 2.4 (ranging from 0.1 to 9.5) years. Results: We diagnosed endometriosis in 23 of the 50 subjects (46%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…10 This is of particular importance for adolescents being diagnosed with and treated for obstructive anomalies, where more than 50% may have evidence of endometriosis at the time of surgical management. 11 Appropriate treatment of endometriosis may have beneficial early-life consequences on educational attainment, early career productivity, and comorbid psychological conditions. [12][13][14][15] It is unknown whether concurrent surgical excision of endometriosis at the time of surgical correction of obstructive anomalies is associated with long-term improvement in reproductive outcomes.…”
Section: Presentationmentioning
confidence: 99%
“…10 This is of particular importance for adolescents being diagnosed with and treated for obstructive anomalies, where more than 50% may have evidence of endometriosis at the time of surgical management. 11 Appropriate treatment of endometriosis may have beneficial early-life consequences on educational attainment, early career productivity, and comorbid psychological conditions. [12][13][14][15] It is unknown whether concurrent surgical excision of endometriosis at the time of surgical correction of obstructive anomalies is associated with long-term improvement in reproductive outcomes.…”
Section: Presentationmentioning
confidence: 99%
“…23 Specific anomalies may further increase the risk of endometriosis; a higher proportion of adolescents with cervical aplasia were diagnosed with endometriosis compared with those with other anomalies. 23…”
Section: Examination and Imagingmentioning
confidence: 99%
“…In one study, authors laparoscopically confirmed endometriosis in 23 of 50 (46%) adolescents undergoing surgical treatment for obstructive reproductive anomalies after menarche. 23 Specific anomalies may further increase the risk of endometriosis; a higher proportion of adolescents with cervical aplasia were diagnosed with endometriosis compared with those with other anomalies. 23 When obtaining a pelvic ultrasonogram, a transabdominal approach should be the initial choice to minimize discomfort.…”
Section: Examination and Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Matalliotakis et al reported that the congenital structural abnormality of the reproductive organs was observed much more in the younger cases (16/55, 32%), compared with the older cases (14/485, 1.6%) [ 5 ]. Another study reported that endometriosis was diagnosed in 23/50 (46%) of patients with obstructive Müllerian anomalies [ 6 ]. On the other hand, patients without Müllerian anomalies can also develop endometriosis at young ages.…”
Section: Introductionmentioning
confidence: 99%